The wet scavenging of air pollutants through artificial precipitation enhancement: A case study in the Yangtze River Delta - Wu, Yixuan; Wang, Yuying; Zhou, Yuquan; Liu, Xiaoli; Tang, Yahui; Wang, Yuxiang; Zhang, Rui; Li, Zhanqing (Frontiers in Environmental Science, 2022)
Taking an aircraft precipitation enhancement operation in the Yangtze River Delta region of China on November 1, 2020, as an example, this study investigates the impact of artificial precipitation enhancement on the wet scavenging of air pollutants using regional meteorological and environmental data and the comprehensive field observation data at the Nanjing University of Information Science and Technology (NUIST) campus site. The results show that the affected area of this operation covers some areas in Anhui and Jiangsu provinces. The precipitation ratio between the target and contrast areas is always greater than 1, indicating the effectiveness of the seeding operation of silver iodide for precipitation enhancement. The regional analysis of air pollutants suggests that the enhanced precipitation can prevent the increase of air pollutants, especially for the particle mattes. The impact of enhanced precipitation on regional trace gases is complex because they are easily affected by the primary emissions. More data analysis at NUIST indicates that two cloud layers appear before the precipitation and merge into one thick cloud layer during the precipitation likely due to the impact of catalysis operation on the upper cloud. After the precipitation, the number concentration of aerosols with a diameter lower than 300 nm reduces significantly, the mass concentration of particle matter with an aerodynamic diameter less than 2.5 μm decreases by about 39%, and the mass concentrations of nitrogen dioxide, sulfur dioxide, and carbon monoxide also decrease in different degrees. These results indicate that it is effective to reduce air pollutants by artificial precipitation enhancement. More studies are needed in the future.